The Parody Mass and the Rethorical-Pedagogical Principle of Imitation - Marisi Rossella (Sciendo, 2021)
In the sixteenth century, composing a parody Mass was a means to pay tribute to an admired piece and master the composing techniques shown therein. The parody Mass is grounded on the principles of imitation and emulation, on which the whole Renaissance rhetoric is based. This article analyses the Missa Quem dicunt homines by Palestrina. It stresses that in the Renaissance a musician could choose to compose a parody Mass, instead of a Mass on cantus firmus, not only to go towards the taste of his clients, and to suit his own preferences, but also to adhere to a certain rhetorical-pedagogical school of thought.